Revitalization Of Aksara Jawa As A Cultural Identity Through Contemporary Typography Design - Yunanto, Yohanes Andri Hervian; Kristianto , Vinsensius Ipung (CV. Publikasi Indonesia, 2025)
The design of Javanese script in the blackletter style represents an exploration of typography that bridges local tradition with global aesthetics. By adapting key principles of blackletter such as bold vertical strokes, contrasting thick-and-thin modulation, and diamond-shaped serifs, the Javanese script undergoes a significant visual transformation. The results demonstrate a shift in character from curvilinear, fluid, and organic forms toward a more rigid, monumental, and Gothic expression. In terms of legibility, this adaptation presents challenges due to the condensed letter structure and narrowed counters; however, aesthetically, it introduces a new visual dialectic that enriches the field of typography. Beyond its function as a reading medium, this style also holds potential for application in contemporary graphic design, such as posters and book covers. Thus, the blackletter-inspired Javanese script can be positioned not only as an experimental typographic design affirming cultural identity, but also as a contribution to the revitalization of Javanese script in the contemporary era.